2014
DOI: 10.1371/journal.pone.0096417
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of QTLs for Late Blight Resistance in the Tomato Accession L3708 Using a Restriction Site Associated DNA (RAD) Linkage Map and Highly Aggressive Isolates of Phytophthora infestans

Abstract: Tomato late blight caused by the oomycete pathogen Phytophthora infestans (Mont.) de Bary is a major threat to tomato production in cool and wet environments. Intensified outbreaks of late blight have been observed globally from the 1980s, and are associated with migration of new and more aggressive populations of P. infestans in the field. The objective of this study was to reassess late blight resistance in the wild tomato accession L3708 (Solanum pimpinellifolium L.) against pathogens of different aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 43 publications
1
34
2
Order By: Relevance
“…The current number of SNPs is also much lower than discovered by Causse et al [16] (16,000 SNPs) and Kim et al [17] (4,680,647); however, these SNPs were not validated. The average frequency of SNPs identified in this study was 1 SNP per 256.4 kb, much higher than reported for the S. lycopersicum  ×  S. pimpinellifolium linkage maps of Salinan et al [13] (1 SNP per 8,482 kb), Capel et al [14] (1 SNP per 4,077 kb) and Chen et al [15] (1 SNP per 1,821 kb). Thus, the present research demonstrated that the GBS approach was efficient in constructing a SNP-based physical map of sufficient resolution for QTL mapping in tomato.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…The current number of SNPs is also much lower than discovered by Causse et al [16] (16,000 SNPs) and Kim et al [17] (4,680,647); however, these SNPs were not validated. The average frequency of SNPs identified in this study was 1 SNP per 256.4 kb, much higher than reported for the S. lycopersicum  ×  S. pimpinellifolium linkage maps of Salinan et al [13] (1 SNP per 8,482 kb), Capel et al [14] (1 SNP per 4,077 kb) and Chen et al [15] (1 SNP per 1,821 kb). Thus, the present research demonstrated that the GBS approach was efficient in constructing a SNP-based physical map of sufficient resolution for QTL mapping in tomato.…”
Section: Discussioncontrasting
confidence: 65%
“…Nevertheless, a sufficient number of validated SNP markers (3,125 SNPs) remained and were found to be useful for QTL mapping. In comparison with previous work, this study discovered fewer validated SNPs than are available in The Solanaceae Genomics Network database (9,226 SNPs) and those reported by Chen et al [15] (4,697 SNPs). The current number of SNPs is also much lower than discovered by Causse et al [16] (16,000 SNPs) and Kim et al [17] (4,680,647); however, these SNPs were not validated.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations